Single and multi-band electromagnetically induced transparency-like effects with a four-fold symmetric metamaterial design. (6th February 2019) - Bagci, Fulya; Akaoglu, Baris
Abstract: In this study classical analogues of single and multi-band electromagnetically induced transparency in metamaterials are numerically and experimentally demonstrated. The unit cells of the two single-band electromagnetically induced transparency-like metamaterials are composed of a Jerusalem cross resonator and four spiral resonators, acting as bright and quasi-dark resonator, respectively. Polarization independent slow light response with transparencies exceeding 80% and group indices more than 100 and 50 are obtained for the proposed first and second electromagnetically induced transparency-like metamaterials, respectively. Supercell method is adopted to achieve polarization independent dual-band electromagnetically induced transparency-like behaviour by combining the unit cells of the designed two electromagnetically induced transparency-like metamaterials in four-fold symmetry. High group indices at the three transmission peaks are obtained with group index values of 114, 127 and 46. Since the third transmission band is not due to classical analogue of electromagnetically induced transparency, a comparison of slow light feature between two transmission bands of different origin is given. The effect of oblique incidence is also investigated and it has been found that the bandwidth and group index properties show opposite behaviour under orthogonal polarizations. Numerical results are supported with experimental measurements for the single and dual-band electromagnetically induced transparency-like metamaterials. The results may be important for practically designing multi-band polarization independent electromagnetically induced transparency-like metamaterials, which have potential applications in multi-frequency filtering, enhanced sensing and multi-band slow light devices.